Use of presumptive recommendations and other strategies to encourage HPV vaccine uptake: Results from a national survey of primary care health professionals - Anna A. Ilyasova; Tara L. Queen; Melissa Gilkey; Benjamin N. Fogel; Olufeyisayo O. Odebunmi; Juan Yanguela; Assanatou Bamogo; Yeshaben Patel; Erin Laurie; Sachiko Ozawa; Stephanie B. Wheeler; Lisa P. Spees (PLoS ONE, 2025)
Background Primary care health professionals’ (PCHPs’) use of presumptive recommendations, which assume parents want to vaccinate, is associated with greater HPV vaccine uptake. We analyzed PCHP characteristics associated with using this and other strategies to encourage HPV vaccination to inform future communication interventions. Methods A national sample of 2,527 PCHPs (26% pediatricians, 22% family physicians, 24% advanced practitioners, 28% nursing staff) completed our survey in 2022. PCHPs reported which of six communication strategies, including presumptive recommendation, they used to encourage HPV vaccination. Multivariable regression models identified PCHP characteristics associated with use of each strategy. Results Overall, 58% of PCHPs used presumptive recommendations. Use of presumptive recommendations was more common among pediatricians (74%) than family physicians (57%), advanced practice providers (54%), or nursing staff (48%, all p < .05). Pediatricians were also more likely than nurses to use prepared talking points, patient stories, motivational interviewing, and offer vaccination another day to hesitant caregivers. PCHPs who had received training on how to introduce HPV vaccination and address parental hesitancy were more likely to use presumptive recommendations (65% vs. 55%, and 67% vs. 53%, respectively). Conclusions Our findings suggest that PCHPs, particularly non-pediatricians, could benefit from additional training on evidence-based HPV vaccination communication strategies.